Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1111/j.1742-4658.2007.06164.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of annealing time of an ice crystal on the activity of type III antifreeze protein

Abstract: Antifreeze proteins (AFPs) are a structurally diverse class of macromolecules that interact with water molecules located in the surface of an ice crystal at temperatures below the melting point of the solution [1]. Interaction of a substantial number of AFPs with the ice surface modifies the shape of the ice crystal, resulting in unique morphologies, such as a hexagonal bipyramid or hexagonal trapezohedron [2]. AFPs inhibit ice growth by adsorbing onto the ice surface (adsorption-inhibition model) [3,4] as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
100
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(105 citation statements)
references
References 26 publications
(42 reference statements)
5
100
0
Order By: Relevance
“…The activity measured in vitro is likely to be a significant underestimation of the natural activity because the cooling rate and the initial ice crystal size are greater than those occurring in nature. It has been demonstrated that these two parameters are inversely proportional to the thermal hysteresis activity measured by experiment (48). Importantly, whereas other hyperactive antifreeze proteins have proven difficult to produce in large quantities, RiAFP is expressed in E. coli at concentrations of up to 50 mg/liter of cell culture (24).…”
Section: Resultsmentioning
confidence: 99%
“…The activity measured in vitro is likely to be a significant underestimation of the natural activity because the cooling rate and the initial ice crystal size are greater than those occurring in nature. It has been demonstrated that these two parameters are inversely proportional to the thermal hysteresis activity measured by experiment (48). Importantly, whereas other hyperactive antifreeze proteins have proven difficult to produce in large quantities, RiAFP is expressed in E. coli at concentrations of up to 50 mg/liter of cell culture (24).…”
Section: Resultsmentioning
confidence: 99%
“…The existence of a slow adsorption and desorption rates was suggested recently by Kubota to explain the time-dependent behavior of the FH activity (34). The dynamic nature of the AFP adsorption was previously reported by other groups for two moderately active AFPs (35,36). Thus, to ensure that the ice surface is well protected by AFPs, we exposed ice crystals to high concentrations of GFPTmAFP for at least 10 min before removing AFPs from the solution.…”
Section: Discussionmentioning
confidence: 99%
“…66 Seven microliters of AFP dissolved in 20 mM Tris-HCl with 4 mM EDTA (pH 8.0) was placed in a glass capillary tube with an inner diameter of 0.92 mm (outer diameter of 1.39 mm) and length of approximately 6 mm. After each end of the tube was sealed with mineral oil, the capillary tube was placed in a copper capillary holder.…”
Section: Measurement Of Thermal Hysteresis and Ice Crystal Morphologymentioning
confidence: 99%